42.3k views
2 votes
Help me solve this question please​

Help me solve this question please​-example-1

1 Answer

2 votes

Answer:

see explanation

Explanation:

there is a difference of - 9 between the 3rd and 4th terms. indicating the sequence could be arithmetic , then

a₂ - a₁ = a₃ - a₂ , that is

k - 17 = - 1 - k ( add k to both sides )

2k - 17 = - 1 ( add 17 to both sides )

2k = 16 ( divide both sides by 2 )

k = 8

The sequence is 17, 8, - 1, - 10

The nth term of an arithmetic sequence is


a_(n) = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

Here a₁ = 17 and d = - 9 , then


a_(n) = 17 - 9(n - 1) = 17 - 9n + 9 = 26 - 9n

User Mathew Byrne
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.